Partisipasi Masyarakat dalam Pengembangan Kawasan Objek Wisata Sajuta Jajang - Maulana Putra (Universitas Merdeka Malang, 2024)
This research aims to determine community participation in their contribution to developing tourist attractions. This qualitative research method with a case study approach involves key informants and ordinary informants. Data collection can be done through observation and interviews. Data analysis takes the form of a process of analyzing interview results, observations and documentation results. The results of the research can be concluded that those involved in developing the Sajuta Janjang tourist attraction area were the people there, especially Jorong Tabek Sarik'an, as well as several elements from the local government. The development of tourist attraction area started with public awareness. The reasons why the community participates in the development of the Sajuta Janjang tourist attraction area can be divided into two, namely from an economic and social perspective. The efforts made include the formation of an agency by the nagari government so that the development of the Sajuta Janjang tourist area runs smoothly and the formation of a buek arek judicial institution to protect local communities and tourists from wrongdoing.